Performance Analysis of MQTT and HTTP Protocols on Low-Power ESP32 Devices for IoT Applications - Syahrul Adriansyah; Sumarno Sumarno; Ulya Mutiara Nurfuha; Abidzar Giffari; Tsulsi Khoirunisa; Winky Gunsan Subarkah (CoreID Journal, 2026)
The choice of communication protocol is crucial in determining the efficiency and service life of low-power Internet of Things (IoT) devices such as those based on the ESP32, particularly in Smart Home applications. This study aims to conduct a Systematic Literature Review to analyze and compare the performance of MQTT and HTTP on low-power ESP32 microcontrollers, with a primary focus on energy efficiency, latency, and data overhead. By analyzing and synthesizing findings from various empirical studies, the results of this review are expected to confirm that MQTT, through its lightweight publish–subscribe architecture and minimal data overhead, offers significantly lower power consumption and better latency compared to the verbose request–response model of HTTP. The conclusions drawn from this analysis will provide strong recommendations for developers in selecting the most efficient communication protocol for resource-constrained IoT applications.